Results of Experimental Verification of Ecologic Education of Senior Pupils in the Process of Profile Learning - Oleh Fasolia (Pedagogical Discourse, 2015)
The results of experimental verification of ecologic education of senior pupils in the process of profile education have been examined in the article. The basic approaches to conducting experimental research have been determine, the number of participants of the experiment has been grounded, the necessary level of their ecologic upbringing has been determined. The analysis of the results of the experiment was conducted according to the comparison charts of ecologic upbringing of senior pupils of profile school, formed in educational, upbringing and developing processes. The conclusion about the expediency of using interactive technologies and special methods for the forming the mentioned quality has been made. The trustworthiness of the received results has been proved.